Effects of a physical education intervention programme for ninth-graders on physical activity-related health competence: Findings from the GEKOS cluster randomised controlled trial. (July 2021) - Volk, Carmen; Rosenstiel, Stephanie; Demetriou, Yolanda; Krustrup, Peter; Thiel, Ansgar; Trautwein, Ulrich; Wagner, Wolfgang; Höner, Oliver; Sudeck, Gorden
Abstract: The main purpose of this cluster randomised controlled trial was to investigate the effects of a physical education (PE) intervention programme combining theoretical and practical components on students' knowledge, skills, abilities and motivation related to competence for a healthy active lifestyle. The intervention used learning tasks to combine theory on health and physical fitness with either running/jumping activities or small-sided ball games and was compared to regular PE classes. Forty-eight PE classes were randomly assigned to intervention (IG-run, IG-game play; 27 classes) and control (CG-run, CG-game play; 21 classes) groups. Overall, 841 ninth-graders (51.1% girls, M age  = 14.20, SD  = 0.51) were tested before and after the six-week intervention and in an eight-to-twelve-week follow-up. Students completed a health-related fitness knowledge test, questionnaires on control competence for physical training, health- and fitness-related interest and attitudes, and physical fitness tests. Regressions in structural equation models revealed positive treatment effects of the game play intervention on students' knowledge (βStdY  = 0.33, 99.6% CI [0.12, 0.55]) and control competence for physical training (βStdY  = 0.26, 99.6% CI [0.02, 0.50]) at the post-test. No significant effects were found at the follow-up test. Treatment effects were independent of gender. The results indicate the short-term effectiveness of learning tasks combining theory with ball games in order to develop knowledge and control competence for physical training in PE. Further studies have to clarify how to sustain effects over time and address students' physical fitness and health- and fitness-related interest and attitudes in interventions combining theory and practice. Trial registration: This study was retrospectively registered with the German Clinical Trials Register (DRKS), DRKS-ID: DRKS00016349. Highlights: Health- and fitness-related physical education intervention with follow-up analysis. Combining theory and ball games in physical education fosters fitness knowledge. Learning tasks enhance competence to align physical activity to health. Increasing motivation within teaching theory and practice needs further study.